On Therapeutic Plasma Exchange Against Severe COVID-19-Associated Pneumonia: An Observational Clinical Study - Cegolon, Luca; Einollahi, Behzad; Panahi, Yunes; Imanizadeh, Sina; Rezapour, Mohammad; Javanbakht, Mohammad; Nikpouraghdam, Mohammad; Abolghasemi, Hassan; Mastrangelo, Giuseppe (Frontiers in Nutrition, 2022)
Background. The evidence around the application of therapeutic plasma exchange (TPE) for the management of critically ill COVID-19 patients is still provisional and further investigations are needed to confirm its eventual beneficial effects. Methods. We carried out a single-centered retrospective observational non-placebo-controlled trial enrolling 73 inpatients from Baqiyatallah Hospital in Tehran (Iran) with confirmed diagnosis of COVID-19 pneumonia. These patients were broken down into two groups: Group 1 (N=30) receiving standard of care and Group 2 (N=43) receiving the above regimen plus TPE. The follow-up time was 30 days and all-cause mortality was the endpoint. Results. Deaths were 6 (14%) in Group 2 and 14 (47%) in Group 1. However, disease severity was significantly lower among COVID-19 patients undergoing TPE, confirming that treatment assignment involved a selection bias of patients by severity of COVID-19 at hospital admission. The adjustment for confounding was carried out using severity as covariate in Cox regression models. The univariate Hazard Ratio (HR) of 0.68 (95%CI: 0.26; 1.80; p=0.441) for TPE turned to 1.19 (95%CI: 0.43; 3.29; p=0.741) after adjusting for severity. Conclusions. The lower mortality observed among patients receiving TPE was due to a lower severity of COVID-19 rather than TPE effects. Keywords: Therapeutic plasma exchange (TPE); plasmapheresis; COVID-19; pneumonia; clinical and laboratory indexes; cytokine storm. TRIAL REGISTRATION IRCT registration number: IRCT20080901001165N58 (Iranian Registry of Clinical Trials) Registration date: 2020-05-27, 1399/03/07 (retrospectively registered)